2021
DOI: 10.1155/2021/3995958
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Danggui Shaoyao San via the Mitophagy-Apoptosis Pathway in a Rat Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a serious neurodegenerative disease. While the main pathological characteristic of AD is widely believed to be the accumulation of amyloid-beta (Aβ) in neurons around neurofibrillary plaques, the molecular mechanism of pathological changes is not clear. Traditional Chinese medicine offers many treatments for AD. Among these, Danggui Shaoyao San (DSS) is a classic prescription. In this study, an AD model was established by injecting Aβ 1–42 into the brains of rats, which were then tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The paraffin-embedded tissue blocks were then sectioned into 4 μm thick slices using a paraffin microtome (HM355S, Thermo Scientific, Shanghai, China). To prepare the tissue for immunostaining, the sections underwent steps including deparaffinization, antigen retrieval, blocking, and incubation with primary and secondary antibodies, as described in previous studies [ 15 ]. Specifically, cell transparency techniques were employed, and antigen retrieval was performed to enhance the antigenicity of the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…The paraffin-embedded tissue blocks were then sectioned into 4 μm thick slices using a paraffin microtome (HM355S, Thermo Scientific, Shanghai, China). To prepare the tissue for immunostaining, the sections underwent steps including deparaffinization, antigen retrieval, blocking, and incubation with primary and secondary antibodies, as described in previous studies [ 15 ]. Specifically, cell transparency techniques were employed, and antigen retrieval was performed to enhance the antigenicity of the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…The model group received an equivalent amount of saline by oral gavage. The dosages for the Danggui Shaoyao San group and the decoction groups were calculated based on the original formula of Danggui Shaoyao San (24 g•kg -1 •d -1 ) and adjusted according to the body surface area and previous preliminary studies (Yang et al, 2023).…”
Section: Animal Grouping and Drug Interventionmentioning
confidence: 99%
“…By using a network pharmacology approach, Song Zhenyan investigated the mechanisms of action of DSS in the treatment of AD at the systemic network level and found that the active compounds of DSS interacted with multiple targets and multiple pathways in a synergistic manner, mainly through anti-inflammatory, anti-apoptotic, metabolic enhancement and immune system enhancement pathways to exert important therapeutic effects on AD. 60 Studies have found that DDS could ameliorate the amyloidosis and neuronal degeneration, 61 inhibit neuronal apoptosis by the activation of the PINK1-Parkin-mediated mitophagy signaling pathway, 62 increase the DHA content by up-regulating independent phospholipase A2 (iPLA2) and 15-lipoxygenase (15-LOX) to ameliorate oxidative stress and inflammation, 63 modulate the metabolism of monoamine neurotransmitters and protect the ultrastructure of the cortex changed by aging 64 during in vivo experiments. In conclusion, DSS could ameliorate the deterioration of cognition in SAMP8, especially in female animals.…”
Section: Pharmacodynamic Materials Basis Of As In the Treatment Of Admentioning
confidence: 99%